2021
DOI: 10.1038/s41598-021-99066-6
|View full text |Cite
|
Sign up to set email alerts
|

Toward understanding of the methoxylated flavonoid biosynthesis pathway in Dracocephalum kotschyi Boiss

Abstract: Nowadays, with the development and advancement of next-generation sequencing technologies, a new path has been provided for transcriptomic studies. In this study, the transcriptome of Dracocephalum kotschyi Boiss., as an endemic and endangered plant which is contained a large amount of valuable secondary metabolites with antioxidant and anticancer properties, was sequenced. Then functional annotation and gene ontology analysis for 165,597 assembled transcripts were performed, most were associated with the meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In total, the RT-qPCR results were consistent with the results of the coregulation network analysis. Several research studies have demonstrated a close relationship between metabolite content and mRNA expression level 24 , 25 , 48 52 ). The RT-qPCR analysis has shown that the relative expression of regulatory TFs and genes tended to give higher up-regulation levels in the high-content ecotypes group than in the low-content ecotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, the RT-qPCR results were consistent with the results of the coregulation network analysis. Several research studies have demonstrated a close relationship between metabolite content and mRNA expression level 24 , 25 , 48 52 ). The RT-qPCR analysis has shown that the relative expression of regulatory TFs and genes tended to give higher up-regulation levels in the high-content ecotypes group than in the low-content ecotypes.…”
Section: Resultsmentioning
confidence: 99%
“…A study of the effect of abscisic acid treatment in saffron demonstrated that crocin and safranal contents and the gene expression of CsGT2 and CsLYC were increased coordinately 68 . It seems that a positive correlation would be between metabolite contents and expression profiles in medical plants 24 , 25 , 48 52 . A thorough understanding of their mechanism will be the aim of future research.…”
Section: Discussionmentioning
confidence: 99%
“…SigmaPlot v14.5 (Systat Software, San Jose, CA) was used to visualize the results of functional annotation. A GO Slim metagenomics database was then substituted for the pre-packed GO Slim database in the Trinotate package (Poursalavati et al 2021). Using Trinotate_GO_to_SLIM, gene ontology identifiers were assigned to clusters.…”
Section: Bioinformatics Analysis Pipelinementioning
confidence: 99%
“…Phenolic compounds have anti‐inflammatory, antimicrobial, antiviral, antioxidant, anticancer, and antiallergic properties and play an important role in scavenging free radicals, quenching singlet oxygen, and decomposing peroxide in biotic and abiotic stress conditions. Also, phenolic compounds mediate the phenylpropanoid pathway, which play an important role in flavonoid production, lignin biosynthesis, and tolerance to environmental stresses (Moradi et al, 2020; Poursalavati et al, 2021). Albeit, the extent of accumulation of phenolic compounds in the stressed plants varies with plant species and type, duration, and intensity of stress.…”
Section: Introductionmentioning
confidence: 99%